Relevansi Pemikiran Seyyed Hossein Nasr Terhadap Pengembangan Paradigma Pendidikan Islam Kontemporer - Abu Mamur (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2025)
This article examines the relevance of his ideas in constructing a contemporary paradigm of Islamic education through three main focuses: (1) the view of human beings as theomorphic creatures; (2) the conception of the teacher–student relationship; and (3) the epistemology of scientia sacra as the basis of sacred and holistic education. The research method employed is library research with a qualitative approach through content and thematic analysis of Nasr’s works and related academic literature. The findings indicate that human beings are viewed as theomorphic creatures reflecting the Divine Names and Attributes, so education should not be reduced to mere information transfer but directed toward tazkir (remembrance) and tazkiyatun nafs (inner purification) so that humans may realize their sacred origin. The teacher–student relationship is positioned in a transcendental framework, where the teacher acts not only as a muʿallim who imparts knowledge but also as a murabbi and spiritual guide, while the student is seen as a ṭālib al-ḥaqq (seeker of truth) journeying through purification of the soul. Nasr’s educational paradigm is transcendental, offering a critique of the secularized and fragmented nature of modern education, and is highly relevant to Islamic education in Indonesia in shaping the complete human being: intellectually intelligent, morally upright, and spiritually enlightened.